A User-Centric Design Approach to Understand International Education in the Contemporary World: Motivations and Gender Preferences for Studying in Europe. (April 2020) - Donkor, Felix Kwabena; Mazumder, Ram Krishna; Hosseinzadeh, Saeed; Roy, Someshwar
Education holds promise as a vehicle for sustainable global development and human capacity development, as reflected in the Sustainable Development Goals set by the United Nations. International education has become a prominent feature in contemporary times on the educational landscape as students become increasingly mobile in pursuit of their right to education. This study investigates the key factors that motivate international students to undertake better quality education at higher education (university) level, particularly in Europe, and the underlying gender preferences for study destinations within the framework of push-pull factors. The study collected responses of 288 individuals from 84 countries who had undertaken some form of education in Europe through the European Commission-funded Erasmus Mundus (EM) Scholarship. Responses were collected through an online platform, Survey Monkey. Outcomes of the study revealed that Germany, United Kingdom, Sweden, Netherlands, and Spain are the most popular destinations for pursuing higher education in Europe. The United Kingdom is the most preferred destination for female students while Germany is the most preferred destination for male students, with slight changes for other countries. Key motivating factors for international education were found to be scholarship opportunity, better quality of education, and availability of the relevant study program. The least influencing factors were found to be the commonality of language, suitable environment (eg climate, temperature), geographical proximity, the scope of migration, and social cost.